Significance of 3U CubeSat OrigamiSat-1 for space demonstration of multifunctional deployable membrane. (August 2020) - Ikeya, Kosuke; Sakamoto, Hiraku; Nakanishi, Hiroki; Furuya, Hiroshi; Tomura, Takashi; Ide, Ryoga; Iijima, Ryo; Iwasaki, Yohei; Ohno, Keigo; Omoto, Keisuke; Furuya, Takashi; Hayashi, Teruaki; et al.
Abstract: The 3U CubeSat OrigamiSat-1 has been developed and launched into orbit in January 2019 to demonstrate a "multifunctional" membrane deployable space structure technology in orbit. Thin-film devices attached throughout the membrane will enable innovative space systems, such as ultralightweight array antennas and solar arrays. The CubeSat's main mission consists of (i) multifunctional membrane deployment mission, and (ii) deployable structure experiment platform mission to enable successive on-orbit demonstrations by CubeSats. This paper describes the significance of these technology demonstrations, and the system design achieved through various prototyping and testing. It also describes the development process and on-orbit operation experience, which will be useful information for other nano-satellite projects that aim at demonstrating innovative technologies actually in space. Highlights: OrigamiSat-1 is a 3U CubeSat for the demonstration of a membrane space structure. Membrane deployment is its primary mission. Deployable structure experiment platform mission is another object of the satellite. The satellite's design, development process, and operation experience are provided.